Rapidly progressive ischemic strokes and transient antiphospholipid syndrome during a mild SARS-CoV-2 infection - Sartor, Roberto; Capozzoli, Francesca; Venturini, Sergio; Crapis, Massimo; Passadore, Paolo; Valente, Mariarosaria (Acta Biomedica Atenei Parmensis, 2022)
SARS-CoV-2 infection is associated with an increased risk of thrombotic events, especially during severe forms of disease. Here we describe the clinical history of a patient with a mild form of Covid-19 infection presenting with multiple cerebral ischemic lesions that evolved in an atypical way.